Beyond antivirals: virus-specific T-cell immunotherapy for BK virus haemorrhagic cystitis and JC virus progressive multifocal leukoencephalopathy. Issue 6 (December 2021) - Nelson, Adam S.; Yalamarthi, Niveditha; Yong, Michelle K.; Blyth, Emily
Abstract : Purpose of review: The clinical manifestations of the polyomaviruses BK and JC in immunocompromised patients include BK virus (BKV) induced haemorrhagic cystitis and nephropathy, and JC virus (JCV) associated progressive multifocal leukoencephalopathy (PML) and are typically a consequence of impaired adaptive immunity in the host. To date, little clinical success has been achieved with antiviral agents or other drug therapies to treat these conditions. Here we review the methods and outcomes of the most recent clinical studies utilising adoptive immunotherapy with BK and/or JC virus-specific T-cells (VST) as either prophylaxis or treatment alternatives. Recent findings: In the last 12–18 months, several clinical trials have been published in the post-haemopoietic stem cell transplant (HSCT) setting showing good clinical success with the use of VST for treatment of BK viremia ± haemorrhagic cystitis. Between 82 and 100% clinical response has been observed in haemorrhagic cystitis using either third-party or donor-derived VST. The therapy was well tolerated with few cases of graft versus host disease in HSCT recipients, but immune mediated renal allograft loss was observed in one renal transplant recipient. Studies using BKV/JCV VST to treat PML are hindered by few patients who are sufficiently stable to receive VST. In a condition that otherwise carries such poor prognosis, VST were associated with clearance of JC virus, clinical and radiological improvement in some patients. Immune reconstitution inflammatory syndrome was a noted adverse event. Summary: Restoration of BK and JC virus immunity using VST immunotherapy has shown good clinical outcomes in BKV associated infections. Further evaluation with the administration of VST earlier in the course of disease is warranted for the treatment of BKV associated nephropathy in renal allograft and in JCV PML. In both indications, larger cohorts and standardisation of dosing and outcome measures would be of benefit.